1996
DOI: 10.1016/0887-6177(95)00041-0
|View full text |Cite
|
Sign up to set email alerts
|

Screening for dementia of the alzheimer type in the community: The utility of the clock drawing test

Abstract: This study reports the sensitivity and specificity of the Clock Drawing Test (CDT) for detecting dementia of the Alzheimer type in a community-dwelling sample of elderly subjects. Forty-two patients with clinically diagnosed Alzheimer's disease and 237 cognitively intact subjects were administered the CDT as part of an epidemiological study of aging and dementia. Three individual measures of clock drawing performance (quantitative score, qualitative score, and combined quantitative and qualitative score) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 0 publications
1
41
2
Order By: Relevance
“…Some studies suggested that “uneven number spacing” (Mendez item 5) corresponds to visuospatial difficulty or planning deficit, and that this relates to the parietal or frontal lobe, whereas in the present study, the association of errors in Mendez item 5 was found only with the frontal lobe.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…Some studies suggested that “uneven number spacing” (Mendez item 5) corresponds to visuospatial difficulty or planning deficit, and that this relates to the parietal or frontal lobe, whereas in the present study, the association of errors in Mendez item 5 was found only with the frontal lobe.…”
Section: Discussioncontrasting
confidence: 80%
“…In one error, the patients set the hands at 11:50 instead of 11:10, presumably affected by the direct auditory input of hearing “11” and “10” when instructed. This error is called a “stimulus‐bound response”, and this response is thought to occur as a consequence of frontal lobe dysfunction . In the other error, the patient set the minute hand to a completely different time (the hour hand was set to 11 in most cases).…”
Section: Discussionmentioning
confidence: 99%
“…The utility of different quantitative CDTs to detect change during the various stages of the dementing process needs further investigation and clarification. The consideration of qualitative aspects of performance as well may enhance clinical accuracy (Cahn et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…11 Visuospatial ability was evaluated using the quantitative and qualitative clock-drawing tests. 12 Verbal fluency was assessed using the letter fluency test and category fluency (animal naming) test. Processing speed was assessed using the Digit Symbol subtest of the Wechsler Adult Intelligence Scale-III.…”
Section: Neuropsychological Assessmentsmentioning
confidence: 99%